Prove all derivatives of: $$ f(x)=\frac{1}{1+x} $$ by induction.

Attempt to solve

I compute few derivatives of $f(x)$ so that i can form general expression for induction hypothesis. I compute all derivatives utilizing formula:

$$ \frac{d}{dx}x^n=nx^{n-1} $$

First 4 derivatives are:

$$ f'(x)=(-1)\cdot(1+x)^{-2}\cdot 1 = -\frac{1}{(1+x)^2} $$ $$ f''(x)=(-1)(-2)(1+x)^{-3}\cdot 1 = \frac{2}{(1+x)^3} $$ $$ f'''(x)=(-1)(-2)(-3)(1+x)^{-4}\cdot 1 = -\frac{6}{(1+x)^4} $$ $$ f''''(x)=(-1)(-2)(-3)(-4)(1+x)^{-5} \cdot 1 = \frac{24}{(1+x)^5} $$

Observe that $(-1)(-2)(-3)(-4)\dots (-n)$ can be generalized with:

$$ (-1)(-2)(-3)(-4)\dots(-n) = (-1)^n\cdot n! $$

Expression follows factorial of $n$ except every other value is positive and every other is negative. If i multiply it by $(-1)^n$ it is positive when $n \mod 2 = 0$ and negative when $n \mod 2 \neq 0$.

Rest of the expression can be generalized as:

$$ (1+x)^{-n-1} = (1+x)^{-(n+1)}=\frac{1}{(1+x)^{n+1}} $$

Combining these gives formula in analytic form:

$$ f(n)= \frac{(-1)^n \cdot n!}{(1+x)^{n+1}} $$

I can form induction hypothesis such that:

$$ \frac{d^n}{dx^n}\frac{1}{1+x} = \frac{(-1)^n\cdot n!}{(1+x)^{n+1}} $$

Induction proof

Base case

Base case when $n=0$:

$$ \frac{d^0}{dx^0}\frac{1}{1+x}=\frac{1}{1+x}=\frac{(-1)^0\cdot 0!}{(1+x)^{0+1}} $$

Induction step

$$ \frac{d^n}{dx^n}\frac{1}{1+x} =_{\text{ind.hyp}} \frac{(-1)^n\cdot n!}{(1+x)^{n+1+1}} $$

$$ \frac{d^n}{dx^n}\frac{1}{1+x} = \frac{(-1)^n\cdot n!}{(1+x)^{n+2}} $$

Now the problem is that formula i used for derivation can only be used recursively. I believe this is correct notation for $n$:th derivative but computing one is only defined recursively with formula i used:

$$ \frac{d}{dx} x^n = nx^{n-1} $$

Which is not defined for case:

$$ \frac{d^n}{dx^n}x^n = \text{ undefined} $$

The idea is to show that this recursion can be expressed in analytical form and it is valid for all $n\in \mathbb{Z}+$ by induction. Problem is i don't know how do you express this in recursive form and how do you get from recursion formula to the analytical one.

  • $\begingroup$ All of your work seems fine. I'm not sure why the formula for iterated derivatives of $x^n$ is causing you anxiety, as you're only using it for negative values of $n$ (thus you'll never be in a position of needing the value of $\frac{d^n}{dx^n} x^n$). $\endgroup$ – Connor Harris Oct 4 '18 at 16:40
  • $\begingroup$ I am not sure why you say that $\frac{d^n}{dx^n}x^n$ is undefined. Simply applying it to a couple of values from $\mathbb{Z}^+$ leads to the intuitive expression $\frac{d^n}{dx^n}x^n=n!$ $\endgroup$ – mrtaurho Oct 4 '18 at 16:40

Your hypothesis is


We want to show that


Let's verify:

\begin{align} \frac{d^{n+1}}{dx^{n+1}}\frac1{1+x} &=\frac{d}{dx}\left(\frac{d^n}{dx^n}\frac1{1+x} \right)\\ &=\frac{d}{dx}\left(\frac{(-1)^nn!}{(1+x)^{n+1}} \right) \\ &=(-1)^n(n!) \frac{d}{dx}(1+x)^{-(n+1)} \\ &= (-1)^n(n!) (-(n+1)) (1+x)^{-(n+2)}\\ &=\frac{(-1)^{n+1}(n+1)!}{(1+x)^{n+2}} \end{align}


Your hypothesis should be

$$\frac{\mathrm d^n}{\mathrm dx^n}\frac{1}{1+x} = \frac{(-1)^n n!}{(1+x)^{n+1}}$$

and what you need for your induction step is:

$$\frac{\mathrm d^{n+1}}{\mathrm dx^{n+1}}f(x)= \frac{\mathrm d}{\mathrm dx}\left( \frac{\mathrm d^n}{\mathrm dx^n}f(x)\right) \quad \forall n \ge 0$$


You inductive hypothesis is that $$ \frac{d^nf}{dx^n}=\frac{(-1)^nn!}{(1+x)^{n+1}}. $$

Your inductive step would then be $$ \frac{d^{n+1}f}{dx^{n+1}}=\frac d{dx}\,\frac{d^nf}{dx^n}=\frac d{dx}\left(\frac{(-1)^nn!}{(1+x)^{n+1}}\right) =\frac{-(n+1)(-1)^nn!}{(1+x)^{n+2}}=\frac{(-1)^{n+1}(n+1)!}{(1+x)^{n+2}}, $$ which shows that the formula holds.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.